Perbedaan Kejadian Shivering pada Pasien Sectio Caesarea dengan Metode Spinal Anastesi Enhanced Recovery After Caesarean Surgery (ERACS) dengan Non ERACS - Heri Cahyono; Rahmaya Nova H; Dwi Novitasari (Jurnal Kesehatan Amanah, 2025)
Background: The use of spinal anaesthesia is favoured over general anaesthesia due to the ease of monitoring the risk of complications. Shivering is known as a frequent complication in patients undergoing surgery with spinal anaesthesia with an incidence of 40-70%. The occurrence of shivering must be immediately prevented and overcome so as not to pose a risk that harms the patient, one of which is by implementing Enhanced Recovery After Caesarean Surgery (ERACS). Research purposes: To determine the difference in the incidence of shivering in sectio caesarean patients with spinal anaesthesia method ERACS with Non ERACS. Research method: This study is a comparative descriptive quantitative study with a case control design. The sample was sectio caesarean delivery patients at the Regional Hospital in 2025 as many as 60 people who were divided into two groups, namely the ERACS and Non ERACS groups of 30 people each with quota sampling technique. Data analysis used univariate and bivariate analysis with the Man Whitney test. Results: There is a difference in the incidence of shivering in sectio caesarea patients with spinal anaesthesia method ERACS with Non ERACS (pvalue = 0.035). Suggestion: Sectio caesarea patients are advised to choose the ERACS spinal anaesthesia method so that the incidence of shivering can be minimized